Mobile Colistin Resistance (MCR) Gene, Antimicrobial Resistance: A Global Public Health Threat - Nusrat, Tanzina; Haque, Mainul (Bangladesh Journal of Medical Science, 2019)
Abstract not available Bangladesh Journal of Medical Science Vol.19(1) 2020 p.5-10